MODEL PERADILAN RESTORATIF DALAM SISTEM PERADILAN ANAK (Kajian tentang Praktik Mediasi Pelaku dan Korban dalam Proses Peradilan Anak di Wilayah Hukum Balai Pemasyarakatan Purwokerto) - Angkasa Angkasa; Saryono Hanadi; Muhammad Budi Setyadi (Faculty of Law, Universitas Jenderal Soedirman, 2009)
Legal fundament of implementation of restorative justice in the phase investigation of juvenile justice system in Indonesia stated in article 5 sentence (1) Law No. 8 Year 1981 concerning KUHAP; article 42 Law No. 3 Year 1997 concerning juvenile court, article 16 sentence ( 1) letter (l), sentence (2) and article 18 Law No. 2 Year 2002 concerning Police Department of Republic of Indonesia, Confidential Telegram of Kabareskrim No. Pol. TR/359/DIT,I/VI/2008. Mediation Perpetrator and Victim in the course of Jurisdiction of Child in jurisdiction territory of prison in Purwokerto, in the form of peace among victim and perpetrator of this child, is conducted in inspection phase, is in prosecution phase and inspection of justice have never been conducted by mediation. Implementation of Mediation in case of child in Jurisdiction territory of Bapas Purwokerto, not yet earned a Restorative Justice Model. This Matter is based on fact that goals of this mediation practice tend to only aim to decontrol continuation. Kata kunci: Juvenile Justice System; Restorative Justice Model; Mediation; prison